(untitled) (Mustansiria Dental Journal, 2024)
This study was conducted to evaluate marginal microleakage of two resin eomposite (Glacier resin composite and Filtek P 60 resin composite) either cured with eonventional light cure unit ( Astralis 5) or light emitting diodes (LED) light cure unit »Radii). Forty class V cavities were prepared in 20 extracted second premolars, one buccaly and one palataly in each tooth. Each cavity was located lmm coronal to eementoenamel junction and lmm apical to it. The teeth were randomly divided into 4 groups, each group of five teeth (I0 cavities): Group I was filled with Glacier resin composite and cured with LED curing unit. Group ll filled with Glacier and cured in ith Astralis 5 curing unit. Group lll filled with Filtek P60 resin composite and cured v- ith LED curing unit. Group IV filled with Filtek P 60 and cured with Astralis curing xnit. The teeth were stored in distilled water for seven days. Then the apices of the teeth were sealed with sticky wax and the teeth were covered with two layers of nail vamish except lmm around the restoration. The teeth were immersed in 0.5% basic faehsin dye for 24 hours at 37°C in the incubator and then were longitudinally xctioned in a buccolingual direction and the extent of dye penetration was recorded. The statistical analysis of the result revealed that the use of LED light cure unit, results in highly significant reduction in the microleakage occlusally and gingivally